2002
DOI: 10.1046/j.1365-3024.2002.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Endemically exposed asymptomatic individuals show no increase in the specific Leishmania (Viannia) panamensis‐Th1 immune response in comparison to patients with localized cutaneous leishmaniasis

Abstract: In Colombia, most cases of human cutaneous leishmaniasis are caused by Leishmania (Viannia) panamensis. Interestingly, up to 30% of the exposed population do not suffer from clinical leishmaniasis although it is likely that they are continuously infected with Leishmania parasites. Since it is believed that the induction of efficient Th1 immune responses protects against Leishmania infections both in humans and in animal models, we determined if endemically exposed asymptomatics showed stronger Leishmania-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
4
17
1
1
Order By: Relevance
“…These analyses also showed a dominance of T lymphocytes over B lymphocytes. Using MST for diagnosis, Armijos et al [10], observed that individuals with active CL had measurably higher MST reactions than those with previous infections, while Trujillo et al [11], showed that MST responses were slightly higher in asymptomatic individuals than in patients suffering from CL. However, the Leishmaniaspecific cellular response was similar in both groups [11].…”
Section: Resultsmentioning
confidence: 99%
“…These analyses also showed a dominance of T lymphocytes over B lymphocytes. Using MST for diagnosis, Armijos et al [10], observed that individuals with active CL had measurably higher MST reactions than those with previous infections, while Trujillo et al [11], showed that MST responses were slightly higher in asymptomatic individuals than in patients suffering from CL. However, the Leishmaniaspecific cellular response was similar in both groups [11].…”
Section: Resultsmentioning
confidence: 99%
“…This mixed pattern of immune response observed in patients with active lesions evolved to a Th1 response characterized by the production of IFN-␥ in cured subjects. Other studies have also reported a mixed Th1/Th2 pattern of cytokine production in cutaneous leishmaniasis [4,9]. It seems that a predominant Th1 response is necessary for parasite control and lesion healing, whereas the concomitant presence of IL-4 and IL-10, and probably other regulatory cytokines such as TGF-␤, may contribute to parasite escape, sustenance of inflammatory stimulation, and lesion persistence [9,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous production of IFN-␥, tumor necrosis factor (TNF)-␣, and IL-10 by antigen-stimulated peripheral blood mononucleaer cells (PBMCs) from patients with active lesions [4] and IL-2, IL-4, IL-5, IL-10, and IFN-␥ mRNAs were demonstrated in biopsy samples taken from active lesions [5][6][7][8]. IL-10 expression was also significantly higher in patients who responded poorly to pentamidine treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fagundes et al [13] found 60 individuals with subclinical infections who showed a positive Montenegro skin test, as well as one individual with a positive PCR. Trujillo et al [22] reported that about 30% of the population infected with L. (V.) panamensis did not develop clinical forms. Davies et al [12] reported a subclinical infection rate of about 10% with L. (V.) peruviana.…”
Section: Resultsmentioning
confidence: 99%